2023
DOI: 10.1002/adfm.202211056
|View full text |Cite
|
Sign up to set email alerts
|

Sebum‐Membrane‐Inspired Protein‐Based Bioprotonic Hydrogel for Artificial Skin and Human‐Machine Merging Interface

Abstract: As an on-skin electronic device, artificial skin shows great potential in medical monitoring and personal electronics, which also holds promise to develop human-machine merging interfaces. However, merging artificial skins with human bodies is largely restricted by the dissimilarity of material compositions in existing artificial skins and biological tissues. Naturally conductive protein is a potential material candidate for artificial skins, nevertheless, it suffers from the critical issue of dehydration whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 55 publications
(74 reference statements)
0
42
0
Order By: Relevance
“…When inspiration ended and ready to exhale, the CNT-FME separated from PLA NFMs, resulting in the formation of an electrical potential difference between the PLA NFM and the CNT-FME, which drove the flow of electrons back in the opposite direction of aggregation and gradually restored the original state. 44 The impact of the SREA strategy on the triboelectric properties of TENG is shown in Figure 3g−i, the output voltage of PLA FMs increased from 4.3 V for SP300 to 21.5 V for SP4000 (nearly 5.0-fold increase), the output current increased from 20.5 nA for SP300 to 63.2 nA for SP4000 (over 3.0-fold increase), and the charge quantity of PLA FMs increased from 17.5 to 26.7 nC (over 1.5-fold increase). We calculated the charge density of PLA FMs based on the charge quantity (Figure 3j) and found that the charge density increased from 4.5 μC/m 2 for SP300 to 6.9 μC/m 2 for SP4000, which was crucial for maintaining the stability of surface potentials and ensuring long-term electrostatic adsorption for the self-powered PLA NFMs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When inspiration ended and ready to exhale, the CNT-FME separated from PLA NFMs, resulting in the formation of an electrical potential difference between the PLA NFM and the CNT-FME, which drove the flow of electrons back in the opposite direction of aggregation and gradually restored the original state. 44 The impact of the SREA strategy on the triboelectric properties of TENG is shown in Figure 3g−i, the output voltage of PLA FMs increased from 4.3 V for SP300 to 21.5 V for SP4000 (nearly 5.0-fold increase), the output current increased from 20.5 nA for SP300 to 63.2 nA for SP4000 (over 3.0-fold increase), and the charge quantity of PLA FMs increased from 17.5 to 26.7 nC (over 1.5-fold increase). We calculated the charge density of PLA FMs based on the charge quantity (Figure 3j) and found that the charge density increased from 4.5 μC/m 2 for SP300 to 6.9 μC/m 2 for SP4000, which was crucial for maintaining the stability of surface potentials and ensuring long-term electrostatic adsorption for the self-powered PLA NFMs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The researchers have designed a pure physical cross-linking skin-like hydrogel composed of bovine serum albumin, glycerin and water, which functions in good contact with the human body, and can be completely degraded by enzymes without any toxic residues, showing high biocompatibility. 7 However, at present, such research is very few. First of all, the strength of most natural substances (proteins, polysaccharides, DNA, etc. )…”
Section: Design Strategy and Mechanism Of Skin-like Hydrogelmentioning
confidence: 99%
“…As a natural biological organ, skin is composed of all natural substances, mainly proteins, lipids and water. 7 By imitating skin components and introducing natural substances as network components of hydrogels, skin-like hydrogels with excellent biocompatibility can be effectively developed. Natural components commonly used to introduce skin-like hydrogels include polysaccharides (commonly used sodium alginate, chitosan, hyaluronic acid) and proteins (commonly used bovine serum albumin, silk fibroin, gelatin).…”
Section: Design Strategy and Mechanism Of Skin-like Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…To be specific, compared with rigid electronic devices, epidermal electronics that mimic various properties of human skin can conformally attach onto human skin with irregular surfaces, which is favorable for reducing contact impedance and improving the fidelity of acquired electrophysiological signals [ 9 , 10 , 11 , 12 , 13 ]. More importantly, epidermal electronics can keep its mechanical and electrical properties stable even under severe stretching or twisting, which further makes it suitable for application fields including healthcare monitoring and HMI [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%